Peran Community Learning Center Dalam Meningkatkan Budaya Literasi di Taman Bacaan Masyarakat Kolong Ciputat - Afifatul Azizah; Hinggil Permana (Edumaspul: Jurnal Pendidikan, 2022)
At this time the islamic character seemed to decrease with the times. Technological development and the lack of the role of parents in controlling and supervising children due to career busyness are the main things that can affect a child's character. Other factors that influence it are the lack of Islamic character education within the scope of the family itself. A superior Islamic school is expected to be able to guide children to have an Islamic character. In conducting this research, researchers used the method of studying literature, observation and interviews with a qualitative-descriptive approach. This study aims to determine the role of the principal in fostering Islamic character in grade 6 students. Based on research conducted, the headmaster of al-hikmah Elementary School in Indonesia applied the habituation method to fostering the Islamic character of a student. In addition, Islamic values are always attached to every learning activity in school.